2018
DOI: 10.1111/xen.12405
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal‐stem‐cells‐derived exosomes are important in enhancing porcine islet resistance to hypoxia

Abstract: This study found that hu-MSC-CM could protect NICCs from hypoxia-induced dysfunction, and exosomes played an important role in hypoxic resistance, suggesting a potential strategy to improve islet transplantation outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…Previous reports have illustrated that one of the potential mechanisms that contribute to the protective effect of MSCs is paracrine effects. As shown in our previous studies, exosomes derived from human MSCs protect NICCs from hypoxia‐induced apoptosis, but the mechanism mediating this process remains unclear. MSCs have been reported to secrete various cytokines, including interleukin‐6 (IL‐6), hepatocyte growth factor (HGF) and others .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous reports have illustrated that one of the potential mechanisms that contribute to the protective effect of MSCs is paracrine effects. As shown in our previous studies, exosomes derived from human MSCs protect NICCs from hypoxia‐induced apoptosis, but the mechanism mediating this process remains unclear. MSCs have been reported to secrete various cytokines, including interleukin‐6 (IL‐6), hepatocyte growth factor (HGF) and others .…”
Section: Introductionmentioning
confidence: 81%
“…MSCs were then isolated from umbilical cords, using a recently published protocol, and cultured with alpha‐MEM medium (GE Healthcare) supplemented with 5% (v/v) UltraGROTM‐Advanced cell culture supplement (Helios BioScience) and 2 mmol/L L‐glutamine (GlutaMAXI, Thermo Fisher) at 37°C and 5% CO 2 . The supernatant of passage 3‐5 huc‐MSCs was collected as conditioned medium (huc‐MSC‐CM) as previously described . Briefly, the human umbilical cord‐derived MSCs, at passage 3‐5, were seeded into 100‐mm tissue culture dishes and cultured with complete medium containing serum in incubators under normoxic conditions (20% O 2 , 5% CO 2 and 37°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, hucMSC-EX treatment relieved the destroyed islets, activated the insulin-signaling pathway, and ameliorated insulin resistance in the rats [32]. Similarly, Nie et al found that hucMSC-EXs could protect islet cells from hypoxia-induced injury in vitro, prolong islet cell survival, and improve its function, thus increasing the efficiency of islet transplantation [33].…”
Section: Diabetesmentioning
confidence: 93%
“…To better understand how MSCs protect islet cells, Nie et al evaluated the contribution of MSC‐secreted factors. MSC‐conditioned media (CM) and exosomes reduced cellular apoptosis leading to enhanced cell survival . Additionally, CM and exosomes activated transcriptional programs in islet cells associated with hypoxia tolerance, including hypoxia‐inducible factor 1 alpha (Hif1‐alpha).…”
mentioning
confidence: 99%